2020
DOI: 10.1016/j.icarus.2020.113683
|View full text |Cite
|
Sign up to set email alerts
|

Global maps of Venus nightside mean infrared thermal emissions obtained by VIRTIS on Venus Express

Abstract: One of the striking features about Venus atmosphere is its temporal variability and dynamics, with a chaotic polar vortex, large-scale atmospheric waves, sheared features, and variable winds that depend on local time and possibly orographic features. The aim of this research is to combine data accumulated over several years and obtain a global VENUS LOWER CLOUDS IN THE INFRARED ATMOSPHERIC WINDOWSObservations at different wavelengths, including ultra-violet (UV), visible (VIS) and nearinfrared (NIR) spectral r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
4
3
0
Order By: Relevance
“…As a result, the cloud is relatively thin in middle latitude. The latitudinal distribution of the cloud thickness obtained in the present study is qualitatively consistent with the infrared measurements (Cardesín Moinelo et al, 2008Moinelo et al, , 2020Carlson et al, 1991;Crisp et al, 1991;Haus et al, 2014;Limaye et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the cloud is relatively thin in middle latitude. The latitudinal distribution of the cloud thickness obtained in the present study is qualitatively consistent with the infrared measurements (Cardesín Moinelo et al, 2008Moinelo et al, , 2020Carlson et al, 1991;Crisp et al, 1991;Haus et al, 2014;Limaye et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This cloud model includes condensable gases of H 2 O and H 2 SO 4 , and condensation, evaporation, and sedimentation of sulfuric acid cloud particles. Their model reproduced the latitudinal distributions of the cloud and H 2 O and H 2 SO 4 vapors consistent with the infrared and radio occultation measurements (e.g., Cardesín‐Moinelo et al., 2020; Cottini et al., 2015; Crisp et al., 1991; Kolodner & Steffes, 1998). They also found that the latitudinal cloud distribution is mainly influenced by the mean meridional circulation in low‐ and mid‐latitudes and the transient waves in high latitudes.…”
Section: Introductionsupporting
confidence: 64%
“…The spatial and temporal variation in the Venusian cloud distribution has been studied by observing the near infrared thermal radiation from Venus which illuminates the silhouettes of the cloud deck. It has been shown that the cloud is optically the thickest in high‐latitudes and the thinnest in mid‐latitudes by infrared measurements (e.g., Cardesín‐Moinelo et al., 2020; Carlson et al., 1991; Crisp et al., 1991). Crisp et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative explanation follows recent evidences of that the cloud structure strongly varies with latitude. Both Fourier spectrometry onboard Venera‐15 orbiter (Zasova et al., 2002, 2007) and Venus Express observations (Titov et al., 2018 and references therein; Cardesín‐Moinelo et al., 2020) suggested that in the high (>60°) latitudes, the cloud top descends by about 8 km compared to the low and middle latitudes, aerosol becomes much denser with the scale height at the cloud top decreasing to less than 1 km. In the opaque polar cloud with sharp upper boundary, all wavelengths sound approximately the same altitude close to the cloud top that could explain convergence of wind profiles at high latitudes in Figure 10a.…”
Section: Resultsmentioning
confidence: 99%